Analysis of the accident at Reftinskaya GRES, which occurred on 08/22/2016 - A. S. Avetisyan; D. N. Efimov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. The work is devoted to the study and analysis of the accident on August 22, 2016 at the Reftinskaya GRES, which resulted in the operation of technological protection and, as a result, cascade shutdowns with a violation of the integrity of the UES of Russia. It should be noted that Reftinskaya GRES is one of the largest thermal power plants in Russia, with an installed capacity of 3800 MW.METHODS. Within the framework of the task set, the authors carried out a number of studies aimed at identifying cause-and-effect relationships on the basis of accident investigation acts.RESULTS. The grounds for the occurrence and development of the accident are investigated and the main causes of the accident are identified.CONCLUSION. A unified cause-and-effect diagram of the occurrence and development of an accident was compiled, indicating the events, the time of their occurrence and the links between them.